Peningkatan kemampuan koordinasi mata dan tangan anak usia dini melalui kegiatan membatik dengan lilin - Nurhusna Kamil (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
The aim of the study was to see the effect of wax batik activities on improving hand-eye coordination in early childhood. Data collection techniques with the results of observations and documentation obtained from class teachers. The results of the study showed that after carrying out batik activities with wax with an age range of 5-6 years, this activity could be an alternative that can be used by teachers in the ability to coordinate eyes and hands in children apart from the existing activities. The new finding in this study is information to PAUD teachers that the application of batik with wax can be done to young children, previously this activity was only done for adults such as students and the community. In addition, the media teaching materials used in this study are additional information for teachers to be able to simplify according to the needs of learning so that activities can run according to the conditions and situations of the children.